2018
DOI: 10.1093/mnras/sty1280
|View full text |Cite
|
Sign up to set email alerts
|

New Cepheid variables in the young open clusters Berkeley 51 and Berkeley 55

Abstract: For guidance on citations see FAQs.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Recently, Lindegren et al (2018) reported a general offset in Gaia parallaxes by -0.029 mas though there is also some evidence that the offset increases for the distances larger than 1 kpc (Stassun & Torres 2018;Lohr et al 2018). This has been further confirmed by many other surveys although with slightly different values (e.g., Schönrich et al 2019;Zinn et al 2019).…”
Section: Parallax Criteria On Membership Selectionmentioning
confidence: 98%
“…Recently, Lindegren et al (2018) reported a general offset in Gaia parallaxes by -0.029 mas though there is also some evidence that the offset increases for the distances larger than 1 kpc (Stassun & Torres 2018;Lohr et al 2018). This has been further confirmed by many other surveys although with slightly different values (e.g., Schönrich et al 2019;Zinn et al 2019).…”
Section: Parallax Criteria On Membership Selectionmentioning
confidence: 98%
“…It has already been employed in many astrophysical contexts, including the study of stars in open clusters 6, but for the TiO γ and bands. (Lohr et al 2018;Alonso-Santiago et al 2019), stars in galaxies of the Local Group (Tabernero et al 2018), and exoplanet host stars (Borsa et al 2021;Demangeon et al 2021).…”
Section: Steparsynmentioning
confidence: 99%
“…Combos for which we obtain 𝑃( 𝐴|𝐵) > 0.01 and that appear at least once in Turner's database, A13 (with membership probability > 0.10 from their work), or Chen, de Grijs, & Deng (2015), together with the spectroscopically confirmed cluster Cepheids described by Lohr et al (2018) and Clark et al (2015), and the association recently found by Negueruela, Dorda, & Marco (2020), are listed at the top of Table A2 (19 in total).…”
Section: Gq Vul and Fsr 0158mentioning
confidence: 90%
“…We rely for this on the cross-survey validation performed by the OGLE team, which also includes targets from the Asteroid Terrestrial-impact Last Alert System survey (ATLAS, Heinze et al 2018) and the All Sky Automated Survey for Supernovae (ASAS-SN, Jayasinghe et al 2018Jayasinghe et al , 2019a surveys. The Cepheids discovered by Clark et al (2015) in the cluster BH 222 and by Lohr et al (2018)…”
Section: Cepheids Samplementioning
confidence: 99%
See 1 more Smart Citation